2006
DOI: 10.1051/0004-6361:20040443
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of near-Earth asteroids

Abstract: We present spectra and taxonomic classifications of 12 Near-Earth Asteroids (NEAs) and 2 inner Main Belt asteroids. The observations were carried out with the ESO 3.5 m NTT and the Danish 1.54 m telescope at La Silla, Chile. Eleven of the investigated NEAs belong to the S class while only one C-type has been identified. Two NEAs were observed at phase angles larger than 60 • introducing significant phase reddening. In order to allow for comparisons between spectra of asteroids observed at different phase angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…All spectra look featureless for λ < 800 nm and their reddening slopes are summarised in Table 5. Michelsen et al (2006) observed a strong phase reddening in NEO spectra at α > 60 • . Our observations were performed at α ≤ 53 • , thus the phase reddening should not hinder our comparison between asteroids.…”
Section: Spectroscopymentioning
confidence: 87%
“…All spectra look featureless for λ < 800 nm and their reddening slopes are summarised in Table 5. Michelsen et al (2006) observed a strong phase reddening in NEO spectra at α > 60 • . Our observations were performed at α ≤ 53 • , thus the phase reddening should not hinder our comparison between asteroids.…”
Section: Spectroscopymentioning
confidence: 87%
“…The NTT is capable of differential tracking, however previous studies found that for exposure times longer than ∼ 10 minutes, NEAs tend to move out of the slit (Michelsen et al, 2006). Therefore, exposures were limited to 600 s. In the case of the 2.2 m telescope, due to its excellent tracking capability the exposure time for the asteroids was 900 s.…”
Section: Visible Spectramentioning
confidence: 99%
“…The data reduction was performed using ESO-MIDAS following the same procedure described in (e.g., Michelsen et al, 2006;Nathues, 2010). The steps involved in the reduction process are: (1) sky background removal by subtracting A from B and B from A, (2) flat-field correction, (3) median filtering for removal of cosmic hits, (4) extraction of the one-dimensional spectra, (5) wavelength calibration using Helium and Argon arc spectra (for the NTT data) and HgHeRb arc spectra (for the Calar Alto data), (6) extinction correction (for the NTT data), using La Silla's mean extinction curve (Tüg, 1977), (7) co-adding of individual spectra to increase the S/N, (8) division of the asteroids spectrum by the spectrum of a solar analog star, and (9) normalization of the spectra to unity at 0.55 µm.…”
Section: Visible Spectramentioning
confidence: 99%
“…We stress, however, that phase reddening is not yet well understood (see Dahlgren et al 1997;Michelsen et al 2006;Sanchez et al 2012, and references therein), especially for primitive asteroid types. Lumme & Bowell (1981), for example, report a mean phase reddening for C-type asteroids of (0.15 ± 0.12)%/10 3 Å/degree in B − V, while Dahlgren et al (1997) find that the phase reddening effect is negligible for the taxonomic P and D classes.…”
Section: Spectral Analysis and Discussionmentioning
confidence: 83%